Who are they to say? Experiences and legal recognition of victimhood of enforced disappearance in Colombia and El Salvador - Pamel Favre; Mina Caren Rauschenbach; Alejandro Jimenez; Ana Srovin Coralli; Bronwen Webster; Lisa Ott (Torture)
Enforced disappearance (ED) not only affects the persons who are deprived of their liberty, but also their next of kin who do not know what happened to their loved one. Their suffering of not knowing has been coined as “ambiguous loss” within psycho-social scholarship and is regarded in law as a form of inhumane treatment which violates the prohibition of torture. ED is attached to a complex experience of victimhood in victims they struggle for social and political recognition of the injustices they suffered. Using the social science notions of “victimhood” and “recognition” on one hand, and the legal perspectives on the other hand, we address the knowledge gap remaining regarding the interactions of the two viewpoints on the issue of ED. For this paper, we carried out a multidisciplinary analysis of the iterative relationship between both perspectives looking at the historical development of the legal landscape and interviewing victims and search actors in the cases of Colombia and El Salvador. We aim to understand the meanings of recognition and victimhood for victims in Colombia and El Salvador against the backdrop of the legal frameworks and state responses they are subjected to. This analysis offers us also valuable insight into victims’ agency and the meanings they afford to victimhood, as well as how political and social constructions of victimhood may facilitate or hinder victims’ struggles for truth and justice.